Autoimmunity and Cancer—Two Sides of the Same Coin - Sakowska, Justyna; Arcimowicz, Łukasz; Jankowiak, Martyna; Papak, Ines; Markiewicz, Aleksandra; Dziubek, Katarzyna; Kurkowiak, Małgorzata; Kote, Sachin; Kaźmierczak-Siedlecka, Karolina; Połom, Karol; Marek-Trzonkowska, Natalia; Trzonkowski, Piotr (Frontiers in Immunology, 2022)
Autoimmune disease results from immune response against self-antigens, while cancer develops when immune system does not respond to malignant cells. Thus, for years autoimmunity and cancer have been considered as two separate fields of research that do not have a lot in common. However, discovery of immune check points and development of anti-cancer drugs targeting PD-1 (programmed cell death receptor 1) and CTLA-4 (cytotoxic T lymphocyte antigen 4) pathways proved that studying autoimmune diseases can be extremely helpful in development of novel anti-cancer drugs. Therefore, autoimmunity and cancer seem to be just two sides of the same coin. In the current review we broadly discuss how various regulatory cell populations, effector molecules, genetic predisposition, and environmental factors contribute to loss of self-tolerance in autoimmunity or tolerance induction to cancer. With the current paper we also aim to convince the readers that pathways involved in cancer and autoimmune disease development consists of similar molecular players working in opposite directions. Therefore, deep understanding of the two sides of immune tolerance is crucial for proper designing of novel and selective immunotherapies.